Action of the Pan American Health Organisation in the International Drinking Water Supply and Sanitation Decade 1981-1990 (PAHO WashingtonUS, 1991)
Contains a summary of the technical cooperation related to the International Drinking Water Supply and Sanitation Decade supplied by PAHO to the countries of the region between 1979 and 1990.
DC